2021
DOI: 10.3390/biom11121759
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific ADHD-like Behaviour, Altered Metabolic Functions, and Altered EEG Activity in Sialyltransferase ST3GAL5-Deficient Mice

Abstract: A deficiency in GM3-derived gangliosides, resulting from a lack of lactosylceramide-alpha-2,3-sialyltransferase (ST3GAL5), leads to severe neuropathology, including epilepsy and metabolic abnormalities. Disruption of ganglioside production by this enzyme may also have a role in the development of neuropsychiatric disorders. ST3Gal5 knock-out (St3gal5−/−) mice lack a-, b-, and c-series gangliosides, but exhibit no overt neuropathology, possibly owing to the production of compensatory 0-series glycosphingolipids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Naïve St3gal5 −/− male mice exhibited a substantial increase in dominant behaviour, and a similar trend was also found in St3gal5 −/− female mice. Behavioural alterations were accompanied by increased mRNA expression of pro-inflammatory cytokine interleukin-1β (Il-1β) and tumour necrosis factor (Tnf), both in the prefrontal cortex (PFC) and the spleen of St3gal5 −/− animals ( Figure 1 , for methods see [ 57 ]).…”
Section: Modelling Of Ganglioside Deficiency In Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Naïve St3gal5 −/− male mice exhibited a substantial increase in dominant behaviour, and a similar trend was also found in St3gal5 −/− female mice. Behavioural alterations were accompanied by increased mRNA expression of pro-inflammatory cytokine interleukin-1β (Il-1β) and tumour necrosis factor (Tnf), both in the prefrontal cortex (PFC) and the spleen of St3gal5 −/− animals ( Figure 1 , for methods see [ 57 ]).…”
Section: Modelling Of Ganglioside Deficiency In Animalsmentioning
confidence: 99%
“…In another study we found increased locomotor activity in mutants of both sexes, as well as elevated anxiety-like behaviour and decreased exploratory behaviour [ 57 ]. These changes were accompanied by alterations in the expression of insulin receptor (IR) isoforms in the spleen and liver; in male mice, mRNA expression of both the A and B isoforms of IR was increased in wild type animals compared to mutants in both the liver and spleen, while in females, IR-B expression was increased in the livers of mutants.…”
Section: Modelling Of Ganglioside Deficiency In Animalsmentioning
confidence: 99%
See 3 more Smart Citations